The mitochondrial uncoupling as a promising pharmacological target against cancer - Roberto Fernández Acosta; Octavio Piñeros; Gilberto L. Pardo Andreu (Journal of Pharmacy & Pharmacognosy Research, 2019)
Context: Mitochondria represent a key intracellular signalling hub that is emerging as important determinants of numerous aspects of cancer development and progression. In this sense, the organelle constitutes a promising target for the development of novel anticancer agents. Despite the negative history, mitochondrial uncoupling has recently proposed as a pharmacological target against cancer, but little is known about the mechanisms involved.